Model Pembinaan Warga Gereja Berbasis Pendampingan Pastoral - Marbun, Purim (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
In general, the forms of community development in the church are predominantly carried out by creating coaching classes. The pattern that is often encountered by presenting coaching materials by pastors or spiritual coaches to the congregation, generally by presenting them in scheduled teaching. Basically, this adopts a structured coaching class by implementing a coaching curriculum. Pastoral assistance-based Church Community Development is a coaching model that is packaged informally, but its implementation is able to make a positive and direct contribution to the fostered congregation. The research method used in this paper is a qualitative study with an analysis approach of various literature sources. The researcher will build content and present practical steps for pastoral assistance-based church community development. The final result of this study is expected to provide a strategy for the implementation of community development with a mentoring approach.